Penerapan Metode Blended Learning dalam Pembelajaran Sejarah di Kelas XI MA Miftahul Ulum - Muhammad Darwis; Andang Firmansyah; Edwin Mirzachaerulsyah (Peneliti.net, 2022)
The emergence of the Covid-19 outbreak that spread to all corners of the world made the world of education in Indonesia very affected by this outbreak, so schools needed to adapt to a new style, namely by carrying out online (distance) teaching and learning activities. Online learning that has been implemented has not been effective due to limited facilities and also its location in rural areas. The purpose of this study was to determine the application of the Blended Learning method which became an alternative learning at MA Miftahul Ulum Sengkubang Village during the pandemic, including preparation, implementation, constraints, assessment and evaluation. The type of research in this research is descriptive qualitative. The process of data collection is done through observation, interviews and documentation. Stages of data analysis used in the form of data collection, data reduction, data presentation and drawing conclusions. This research result that there are 3 stages in the application of mixed methods (Blended Learning) namely: 1) planning is done by determining learning objectives, providing infrastructure, arranging schedules, socialization and evaluation. 2) the implementation of the learning includes online and face-to-face learning in history and other subjects. 3) assessment and evaluation of the learning system where educators hold meetings which are held once a month. This study found obstacles in the application of the Blended Learning method such as the internet network which is often unstable and the lack of supporting human resources.